Internalisasi Nilai-Nilai Good Amil Governance pada BAZNAS Kabupaten Jember - Nikmatul Masruroh (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) AMIK Indonesia, 2023)
In this article, devotion focuses on two main aspects. First, an analysis of the implementation of Amil Good Governance (GAG) at BAZNAS Jember Regency. Second, the service also examined the model of internalization of GAG values ​​in the organizational structure of BAZNAS Jember Regency. The main objective of this service is firstly to provide effective support during the implementation of GAG at BAZNAS Jember Regency, and secondly, to facilitate the internalization of GAG values ​​through training programs creation and mentoring is held at BAZNAS Jember Regency and the associated zakat management unit. The mentoring approach used in this service is a community-based learning approach that focuses on providing education to the community through a variety of training and practical applications in practice. The results of this service include two main aspects. Firstly, on the implementation of GAG at BAZNAS Jember Regency, the department determined that this was successfully achieved through the application of Good Corporate Governance (GCG) principles, including transparency, accountability Accountability, responsibility, independence, fairness, and equality. Second, the Ministry noted that a sustainable training approach on transparency, periodic use of the SIMBA application, as well as support for the preparation of standard operating procedures (SOPs) for collection and distribution of zakat, have contributes significantly to improving the distribution of zakat. progress. Overall, the results of this service show that the internalization of GAG values ​​can be implemented systematically according to established principles. This process was made possible thanks to the close cooperation between BAZNAS Jember Regency, UIN Kiai Haji Achmad Siddiq Jember, as well as the active role of zakat volunteers in supporting this effort.